SYNTHESIS AND CHEMICAL POTENTIAL OF HYBRID STRUCTURES WITH OXADIAZOLE NUCLEI OF PYRAZOLE AND THIOPHENE - Панасенко, Наталія; Панасенко, Надія (Modern engineering and innovative technologies, 2022)
By cyclocondensation of 4-pyrazolylamidooximes with N-cyanoacetyl-3,5-dimethylpyrazole 3-(4-pyrazolyl)-5-(1,2,4-oxadiazolyl)acetonitriles were synthesized. By interaction of these compounds with sulfur and cycloalkanones in the conditions of Gewald reacti